2016
DOI: 10.1002/oby.21551
|View full text |Cite
|
Sign up to set email alerts
|

Voxel‐based morphometry reveals brain gray matter volume changes in successful dieters

Abstract: Objective To compare regional brain volume predictors of percent weight loss (WL) in dieters with obesity (DwO) and in the same participants categorized as “successful” (>7% WL) or “unsuccessful” dieters (<7% WL). Methods DwO (n=72) or healthy weight (HW) (n=22), and completed a structural MRI at baseline and 3-months. All DwO participants were enrolled in a 12-week program consisting of a reduced calorie diet, increased physical activity, and behavioral modification. We used SPM8-based voxel-based morphomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Neuroimaging has been extensively applied in research on the brain processes associated with obesity risk and responsiveness to weight loss interventions. For example, several studies have examined gray matter (GM) and white matter (WM) volumes as predictors of responsiveness to weight control interventions (Honea et al, 2016; Mokhtari et al, 2016). In addition to structural imaging, functional MRI (fMRI) has been used extensively to examine brain activation differences between obese/overweight individuals and those with normal weight.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging has been extensively applied in research on the brain processes associated with obesity risk and responsiveness to weight loss interventions. For example, several studies have examined gray matter (GM) and white matter (WM) volumes as predictors of responsiveness to weight control interventions (Honea et al, 2016; Mokhtari et al, 2016). In addition to structural imaging, functional MRI (fMRI) has been used extensively to examine brain activation differences between obese/overweight individuals and those with normal weight.…”
Section: Introductionmentioning
confidence: 99%
“…We can use these markers to examine associations between diet- and age-related brain changes that might not be detectable using clinical assessment. A few studies have examined the relationship between a Mediterranean diet and structural neuroimaging markers of gray matter volume such as brain atrophy and cortical thickness [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Luciano et al found that lower adherence to a Mediterranean diet was associated with total brain atrophy over a three-year interval [ 6 ], and Gu et al demonstrated that Mediterranean diet adherence was associated with less brain atrophy, with larger brain volumes of the cingulate cortex, parietal lobe, temporal lobe, and hippocampus, and larger cortical thickness of the superior-frontal region [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown the benefits of diet and physical activity on brain structure in successful dieters. Honea et al found that weight loss percentage correlated positively with baseline gray matter volume in the right parahippocampal and orbitofrontal gyri in obese dieters, concluding that weight loss is related to volumetric changes in brain areas linked to interoception and food motivation [ 12 ]. On the other hand, some studies have examined obesity and cerebral connectivity through functional magnetic resonance with a resting state modality, but very few included a dietary intervention and/or physical exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity-related structural brain abnormalities might be reversible with dietary/lifestyle/surgical/medication interventions fostering weight loss and, especially in adolescents and young adults ( 65 69 ). Structural neuroimaging studies have reported increases in brain volumes following aerobic exercise in healthy subjects as well as in participants with SZ ( 70 ), which may be related to weight reduction ( 67 , 71 ). Also medications targeting obesity may have neuroprotective effects.…”
Section: Discussionmentioning
confidence: 99%